Ethiopians' knowledge of and attitudes toward epilepsy: A systematic review and meta-analysis - Woldegeorgis, Beshada Zerfu; Anjajo, Eyosiyas Abreham; Korga, Tesfalem Israel; Yigezu, Berhanu Lijalem; Bogino, Efa Ambaw; Tema, Habtamu Tieka; Alemu, Henok Berhanu; Boda, Tesfalem Israel; Daba, Dugo Angasa; Gobena, Negeso; Obsa, Mohammed Suleiman (Frontiers in Neurology, 2023)
Abstract Background: Epilepsy remains one of the world's most common neurological diseases, but it appears to be widely misunderstood, particularly in under-resourced countries like Ethiopia. Improving individuals’ knowledge and attitude toward epilepsy is critical for reducing the multifaceted impacts of epilepsy. Therefore, in this study, we sought to estimate the pooled levels of good knowledge and a favorable attitude toward epilepsy and also identify the associated factors using available data collected from different segments of the population. Methods: Articles were searched in international electronic databases. A standardized Microsoft Excel spreadsheet and STATA software version 16 were used for data extraction and analysis, respectively. The Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) checklist was used to write this report. The random-effect meta-analysis model was used to estimate Der Simonian-Laird’s pooled effect. Statistical heterogeneity of the meta-analysis was checked via Higgins and Thompson’s I2 statistics (0-100%), and Cochran’s Q test at P <0.10. Subgroups, based on the study regions, and sensitivity analyses were also performed. Publication bias was examined subjectively using funnel plots and objectively using the nonparametric rank correlation test of Begg and the regression-based test of Egger for small study effects with P < 0.05 considered to indicate potential publication bias. Furthermore, the Trim-and-fill method of Duval and Tweedie was used to explore sources of publication bias for the favorable level of attitudes toward epilepsy. Result: A total of 12 studies with 6373 study participants and 10 studies with 5336 study participants were included to estimate the pooled level of good epilepsy knowledge and favorable attitudes respectively. The overall estimated levels of good epilepsy knowledge and favorable attitudes toward epilepsy among Ethiopians were 47.37 % [(95 % CI: 35.00, 59.74), I2=99.2, P< 0.001] and 46.83 %[(95 % CI: 32.75, 60.90), I2=99.2, P <0.001] respectively. Subgroup analysis revealed that the pooled level of good epilepsy knowledge was 48.51% [(95%CI: 38.95, 58.06), I2=95.6%, P 0.001] in the Amhara region. Conclusion: In the current review, we found out that there is a huge knowledge gap and an unfavorable level of attitudes toward epilepsy, which demand immediate public health action.